Ernesto Sierra: Leopoldo Marechal y José Lezama Lima: Luces y sombras de la ciudad letrada. Editorial Verbum, S. L., 2023, 196 pp. ISBN: 978-84-1337-955-5 - Antonio Correa Iglesias (Philologia Hispalensis)
Reseña de libro: